2020
DOI: 10.1175/wcas-d-19-0109.1
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking the Levels of Household and Individual Climate Change Adaptation: Empirical Evidence from Leeds, United Kingdom

Abstract: This study set out to empirically determine the current state of individual and household adaptation to climate change in the United Kingdom and how policy makers can improve on it. The study utilized both qualitative and quantitative approaches (mixed method). For the quantitative aspect of the study, a quota-sampling technique was employed in the selection of 650 respondents for the study using a well-structured questionnaire. The quota representation was based on age and gender. Data were analyzed using des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In terms of the log of the odds ratio we rewrite the model as the likelihood that a farmer will be in the agroecology group (A i ) with respect to the likelihood that the farmer is not in the agroecology group (1 -A i ) as expounded (Otum Ume et al, 2020). The likelihood that a farmer is non-agroecology group member (1 -A i ) we define as:…”
Section: Econometric Approachmentioning
confidence: 99%
“…In terms of the log of the odds ratio we rewrite the model as the likelihood that a farmer will be in the agroecology group (A i ) with respect to the likelihood that the farmer is not in the agroecology group (1 -A i ) as expounded (Otum Ume et al, 2020). The likelihood that a farmer is non-agroecology group member (1 -A i ) we define as:…”
Section: Econometric Approachmentioning
confidence: 99%
“…Leeds, the biggest city in West Yorkshire, was the first place in the U.K. to launch a climate commission in 2017, while a number of councils declared climate emergencies in 2019. Nevertheless, a recent survey of Leeds residents found that household-scale engagement with adaptation remains low [51].…”
Section: Locationmentioning
confidence: 99%